KPICGS2016 - DEBATES ON RIGHTS OF WOMEN AND GENDER, FEATURES FOR SUSTAINABLE DEVELOPMENT GOALS BY 2030 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 16 November 2016 " Deconstructing and Reconstructing Sustainable Development: Implications for Gender Studies in this Challenging Times" is the theme for this year’s KANITA Postgraduate International Conference on Gender Studies (KPICGS).